Vibration control systems in a building prototype: Application of SMA coil springs in diagonal bracing and TMD. (15th January 2023) - Moraes, Yuri J.O.; Rodrigues, Marcelo C.; Silva, Antonio A.; Grassi, Estephanie N.D.; Araújo, Carlos J.
Highlights: Smart systems effectively damp structure vibrations but the added weight must be limited. SMA springs were used in TMD and diagonal bracing passive vibration control systems. SMA spring length and number maximized vibration absorption and minimized added weight. Shorter SMA springs with higher deformation are more effective in the attenuation. Abstract: The growing concern with the efficiency and reliability of civil structures that are slim, flexible and highly vulnerable to earthquakes, side winds and impacts can be addressed with the use of smart materials. Among the available techniques, passive control stands out due to its low cost, low maintenance, and no need for an external energy source. In this sense, this work proposes the incorporation of NiTi superelastic SMA springs in a diagonal bracing arrangement and as a secondary device in a Tuned Mass Damper (TMD) to improve the passive vibration control of a 3-DOF building prototype. The study compares the efficiency of the proposed control systems through the modal analysis of the structure under scenarios combining different control types (diagonal bracing or TMD), vibration types (impulse excited or base-forced) and passive attenuation (with or without SMA springs). It was concluded that the length of the SMA spring attenuators has a direct influence on the control capacity, with the shorter springs providing a higher attenuation efficiency, as they generate greater mechanical hysteresis and dissipate more mechanical energy, while adding less mass to the structure. In terms of the amplitudes reached in the experimental modal analysis, the TMD with the SMA springs as a secondary device was the most efficient technique, allowing reductions of up to 74% in impulse excitation and 44% in forced vibration. In terms of added mass, TMD also proved to be more effective, reducing about 63% of NiTi SMA material in impulse excitation and 73% in forced vibration, when compared to diagonal bracing.